Zia’s Presidential Powers Under Eighth Amendment and Its Governance Regarding Security of Shia Masses - Syeda Asmat Zahra Naqvi (International Journal on Orange Technologies, 2021)
The paper represents analytical dependences of the precipitation process on the kinematically possible flow velocities that satisfy the boundary conditions and the condition of volume constancy